Lymphocytic RNA stimulates physiological regeneration and enhances microcirculation in the thyroid gland - N. V. Tishevskaya; E. S. Golovneva; R. V. Takhaviev (Вестник трансплантологии и искусственных органов)
Objective: to investigate the regulatory effects of exogenous lymphocyte RNA on thyroid gland regeneration.Materials and methods. The study was conducted on 18 male Wistar rats (310–350 g), divided into three groups (n = 6 per group). Group 1 – intact rats; group 2 – control rats (subjected to 6 weeks of physical activity), group 3 – experimental rats (subjected to 6 weeks of physical activity + RNA injection). Total RNA, isolated from the spleen of a 30-day-old pig, was administered four times at a dose of 30 μg/100 g body weight, once per week. Follicular epithelium and vascular structures were analyzed using morphometry, VEGF content was quantified via immunohistochemistry with specific antibodies, and thyroid microvascular function was assessed using laser flowmetry.Results. Following RNA administration, the relative thyroid gland mass increased by 16%, the folli- cular epithelium area expanded 1.5-fold, and the vasculature area doubled. Additionally, VEGF content increased 2.5-fold compared to intact rats, while microcirculation intensity rose by 64%, and vascular resistance decrea- sed by 21%.Conclusion. Administration of morphogenetically active total RNA under conditions of increased oxygen demand promotes regenerative hypertrophy of the glandular epithelium and enhances microcirculation in the thyroid gland.